Dual signaling pathways of TGF-β superfamily cytokines in hepatocytes: balancing liver homeostasis and disease progression - Chaudhary, Roohi; Weiskirchen, Ralf; Ehrlich, Marcelo; Henis, Yoav I. (Frontiers in Pharmacology, 2025)
The transforming growth factor-β (TGF-β) superfamily (TGF-β-SF) comprises over 30 cytokines, including TGF-β, activins/inhibins, bone morphogenetic proteins (BMPs), and growth differentiation factors (GDFs). These cytokines play critical roles in liver function and disease progression. Here, we discuss Smad-dependent (canonical) and non-Smad pathways activated by these cytokines in a hepatocellular context. We highlight the connection between the deregulation of these pathways or the balance between them and key hepatocellular processes (e.g., proliferation, apoptosis, and epithelial-mesenchymal transition (EMT)). We further discuss their contribution to various chronic liver conditions, such as metabolic dysfunction-associated steatotic liver disease (MASLD), metabolic dysfunction-associated steatohepatitis (MASH), and hepatocellular carcinoma (HCC). In MASLD and MASH, TGF-β signaling contributes to hepatocyte lipid accumulation, cell death and fibrosis progression through both Smad and non-Smad pathways. In HCC, TGF-β and other TGF-β-SF cytokines have a dual role, acting as tumor suppressors or promoters in early vs. advanced stages of tumor progression, respectively. Additionally, we review the involvement of non-Smad pathways in modulating hepatocyte responses to TGF-β-SF cytokines, particularly in the context of chronic liver diseases, as well as the interdependence with other key pathways (cholesterol metabolism, insulin resistance, oxidative stress and lipotoxicity) in MASLD/MASH pathogenesis. The perspectives and insights detailed in this review may assist in determining future research directions and therapeutic targets in liver conditions, including chronic liver diseases and cancer.